GGBFS as potential filler in polyester grout : flexural strength and toughness - Lim, Siong Kang (Elsevier BV, 2009)
The effectiveness of ground granulated blast furnace slag (GGBFS) as filler in polyester resin grout was investigated. The mix proportions of polymer grout was properly designed and manufactured. The binder, hardener and fillers used in this study were isophatalic unsaturated polyester resin (IUPR), methyl ethyl ketone peroxide (MEKP) and river sand as well as GGBFS respectively. The amount of GGBFS incorporated was varied from 10% to 30% of total filler by weight. The performance of the grout was investigated in terms of flexural strength development and durability. Modulus of elasticity test was also conducted in order to study the effect of GGBFS on toughness of the grout. Results were compared with the control grout without the slag as filler. The results showed that the use of GGBFS as filler has improved the performance of polyester resin grout. The grout has proven itself durable against the hostile environment of Malaysia and its performance were similar to that of epoxy resins but very much cheaper than the epoxy resin readily available in the market.